2022
DOI: 10.1057/s41264-022-00170-z
|View full text |Cite
|
Sign up to set email alerts
|

Linking psychological needs, perceived financial well-being and loyalty: the role of commercial banks

Abstract: This research examines the role of commercial banks in influencing customers’ perceived financial well-being under the basic psychological need theory and the impact of customers’ perception of financial health on their bank loyalty. We firstly conducted in-depth interviews to explore bank-related factors that could help satisfy the needs for autonomy, relatedness, and competence that a bank customer may have in their financial life. A structural equation model linking personalization of service offerings, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…, 2006; Phan and Anh, 2019; Presser, 2001). Personalisation of financial service offerings has been found to have a positive effect on financial well-being (Hoang et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2006; Phan and Anh, 2019; Presser, 2001). Personalisation of financial service offerings has been found to have a positive effect on financial well-being (Hoang et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effectiveness of a newsletter can be amplified by including a personalised message that refers to the readers' self (Carvalho et al, 2006;Phan and Anh, 2019;Presser, 2001). Personalisation of financial service offerings has been found to have a positive effect on financial well-being (Hoang et al, 2022). That said, other research has not found a significant difference between personalised and generic messages (Maslowska et al, 2011a).…”
Section: Effects Of Newsletters On Behaviourmentioning
confidence: 99%